Results Of Using Lateral Surgical Approaches In The Surgical Treatment of Tuberculosis Spondylitis of the Lumbar and Lumbosacral Spine - Usmonov Isomiddin Haydarovich; Pardaev Muxammadjon Jumanazarovich (Indonesian Journal of Innovation Studies, 2022)
The work is based on the survey data of 190 patients with tuberculosis spondylitis (TS) of the lumbar and lumbosacral spine, who underwent surgical intervention using traditional lateral access. In 158 (83.2%) patients, radical reconstructive surgery (RRS) was performed in the lumbar, and in 32 (16.8%) cases - lumbosacral spine. Of these, 127 (66.8%) patients of the affected segment underwent spinal fusion using a titanium mesh cage (Piramesh), and 63 (33.2%) using the traditionally classical method with auto bone fusion. The use of traditional lateral access allows the surgeon to fully work in the lumbar spine, but with lesions of the lumbosacral spine, the possibility of detecting VL5, VS1-2 bodies is difficult and dangerous. Damage to muscles, nerves and blood vessels of the abdominal wall, often encountering postoperative complications such as muscle prolapse, abdominal wall hernia, discomfort, and rough scar are considered to be the main disadvantages of lateral access in RVO of the lumbar and lumbosacral spine.